Pairing taVNS and CIMT is feasible and may improve upper extremity function in infants - McGloon, Kelly; Humanitzki, Elizabeth; Brennan, Julia; Summers, Philip; Brennan, Alyssa; George, Mark S.; Badran, Bashar W.; Cribb, Anne R.; Jenkins, Dorothea; Coker-Bolt, Patricia (Frontiers in Pediatrics, 2024)
In this study we combined non-invasive transcutaneous auricular vagal nerve stimulation (taVNS) with 40 hours of constraint induced movement therapy (CIMT) in infants. All infants completed the full intervention with no adverse events. Therapists were able to maintain high treatment fidelity and reported high ratings for ease of use and child tolerance. Preliminary results show promising gains on motor outcomes: Mean QUEST increase 19.17 (minimal clinically important difference, MCID 4.89); Mean GMFM increase 13.33 (MCID 1-3%). Infants also exceeded expectations on Goal Attainment Scores (+1). Early data is promising that taVNS paired with intensive motor CIMT is feasible, reliable, and safe in young infants with hemiplegia, and may help harness activity-dependent plasticity to enhance functional movement.